HAEMOPHILIA: AN OVERVIEW - Nagar, Lokesh Kumar; Sharma, Neha; Khinchi, M. P.; Khan, Mohd. Shahid; Kumar, Atul (Asian Journal of Pharmaceutical Research and Development, 2017)
Haemophilia also called hemophilia, is a mostly inherited, genetic disorder that impairs the body's ability to make blood clots, a process needed to stop bleeding. This results in people bleeding longer after an injury, easy bruising, and an increased risk of bleeding inside joints or the brain. Those with mild disease may only have symptoms after an accident or during surgery. Bleeding into a joint can result in permanent damage while bleeding in the brain can result in long term headaches, seizures, or a decreased level of consciousness.There are two main types of haemophilia, haemophilia A due to not enough clotting factor VIII and haemophilia B due to not enough clotting factor IX. They are typically due to inheriting from one's parents an X chromosome with a non functional gene.